Quantitation of isobaric phosphatidylcholine species in human plasma using a hybrid quadrupole linear ion-trap mass spectrometer - Zacek, Petr; Bukowski, Michael; Rosenberger, Thad A; Picklo, Matthew (Journal of lipid research, 2016)
Phosphatidylcholine (PC) species in human plasma are used as biomarkers of disease. PC biomarkers are often limited by the inability to separate isobaric PCs. In this work, we developed a targeted shotgun approach for analysis of isobaric and isomeric PCs. This approach is comprised of two MS methods: a precursor ion scanning (PIS) of mass m/z 184 in positive mode (PIS m/z +184) and MS3 fragmentation in negative mode, both performed on the same instrument, a hybrid triple quadrupole ion-trap mass spectrometer. The MS3 experiment identified the FA composition and the relative abundance of isobaric and sn-1, sn-2 positional isomeric PC species, which were subsequently combined with absolute quantitative data obtained by PIS m/z +184 scan. This approach was applied to the analysis of a National Institute of Standards and Technology human blood plasma standard reference material (SRM 1950). We quantified more than 70 PCs and confirmed that a majority are present in isobaric and isomeric mixtures. The FA content determined by this method was comparable to that obtained using GC with flame ionization detection, supporting the quantitative nature of this MS method. This methodology will provide more in-depth biomarker information for clinical and mechanistic studies.
Keywords: shotgun lipidomics; National Institute of Standards and Technology human blood plasma; mass spectrometry; Phosphatidylcholines; Reference Standards; docosahexaenoic acid; Humans; Biomarkers; referenční standardy; Mass Spectrometry; fosfatidylcholiny; biologické markery; hmotnostní spektrometrie; triple quadrupole/ion-trap; lidé